Analysis of biologically active constituents from water and methanol soluble extracts of reishi mushroom (Ganoclerma lucidum)" - Goh, Yung, Shin (Universiti Sains Malaysia, 2006)
Ganoderma lucidum is one of the treasures of Chinese medicine. It has attained an unparalleled reputation in the Orient as the ultimate herbal substance. In this study, a rapid and efficient method for the extraction of bioactive molecules in Ganoderma Jucidum is described. This method is based on the extraction of Ganoderma lucidum with hot water, methanol and a 1:1 v/v mixture of hot water-methanol. The FT-IR spectra of Ganoderma lucidum and its extracts were recorded in potassium bromide (KBr) over the range of 4, 000-400 cm-1 . The UVVisible spectrophotometric measurements were performed in water and methanol over the range of 200-800 nm. Bioactive elements in the aciddigested Ganoderrna lucidum samples were determined by flame atomic absorption spectroscopy (AAS). The FT-IR spectra of Ganoderma lucidum and its extracts exhibited characteristic absorption bands with significant difference in their number and position. The infrared spectral bands indicated presence of functional groups attributed to polysaccharides, amino acids, vitamins, terpanes and enzymes moieties. The UV-Visible spectra, however, could not give much information on the structure of the compounds extracted, due to very complex nature of biological molecules. The concentration of elements determined in Ganoderma lucidum by flame AAS was found for Na 12.5 ± 0.001 mg/L, K 210.4 ± 0.003 mg/L, Ca 23.9 ± 0.001 mg/L, Mg 7.1 ± 0.005 mg/L, Zn 1.9 ± 0.001 mg/L and Fe 1.2 ± 0.004 mg/L.